THE ROLE OF PARENTS ON READING ABILITY IN PULAU KOMANG SENTAJO ELEMENTARY SCHOOL STUDENTS - Mai Danti Rizkiana (Yayasan Thaifah Manshurah Pekanbaru, 2023)
Abstract: This study aims to describe the role of parents on the reading ability of elementary school students. This type of research is a case study, namely on two parents who have elementary school age children who do not yet have the ability to read well. This research was conducted in Koto Tuo Hamlet, RT 002 RW 002, Pulau Komang Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency. The data collection techniques in this study were by conducting interviews, observations, and documentation. Data analysis techniques that researchers use are data reduction, data presentation, and conclusions. Based on the results of the study, it was found that the role of parents on the reading ability in Pulau Komang Sentajo Elementary School students was good and some were still not. Of the two parents, there is one parent who has carried out his role well, and one parent who is still not good at carrying out his role. This can be seen from the research indicators, namely parents as educators, parents as teachers, parents as motivators, parents as facilitators, parents as supporters, and parents as models for children's reading skills. Keywords: Role of Parents, Reading Ability